(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The concept of human dignity is nowadays challenged by new problems and questions stemming from the bioethical debate. After the formal inclusion of this principle in the post-WWII Constitutions, the need to re-open the discussion on both the meaning and the limits of human dignity has been urged by the scientific and medical progress. The article underlines the development of “human dignity”, from its Christian origins to its philosophical and historical studies. Starting from this unavoidable premise and through the looking glass offered by some leading cases concerning embryos’ rights, this paper aims at analyzing the new challenges that the Constitutionalism and the concept of human dignity are increasingly called to tackle.